(untitled) (Prima Journal of Integrated Studies, 2026)
This article examines the transformative role of artificial intelligence (AI) in contemporary education. Based on a critical synthesis of four empirical studies conducted in Russia, Iran, Indonesia, and China, the paper analyzes the adaptive potential of AI, the risks of algorithmic bias, and cultural irrelevance. A three-level hybrid model for the distribution of functions between the teacher and neural networks is proposed (technical-diagnostic, interpretative-adaptive, and motivational-reflective levels). It is argued that the effectiveness of the educational system in the digital age is determined not by the power of AI but by the quality of pedagogical design and the preservation of human-centered values.